Technical performance scores associate with early prognosis of tetralogy of Fallot repair - Alifu, Ailixiati; Wang, Haifan; Chen, Renwei (Frontiers in Pediatrics, 2024)
Objective: This study aimed to investigate the relationship between technical performance scores (TPS) and the early prognosis of tetralogy of Fallot repair (TOF). Methods: A retrospective study was conducted on TOF repair patients at our center from Oct 2017 to Oct 2022. Patients were classified into Class 1 (no residua), Class 2 (minor residua), or Class 3 (major residua) based on TPS derived from predischarge echocardiograms and need for reintervention. Statistical methods were used to assess the association between TPS and early prognosis. Results: A total of 75 TOF repair patients (40% female, 60% male) were analyzed and categorized into TPS1 (24%), TPS2 (53.3%), and TPS3 (22.6%) based on pre-discharge echocardiographic findings. The median follow-up time was 7.0 months. The multivariable Cox regression analysis indicated that TPS3 scores are associated with a 12.68-fold increase in risk compared to TPS1 and TPS2 scores (95% CI = 12.68 (0.9 179.28), P=0.06). The Spearman rank correlation analysis revealed a weak positive correlation between TPS classification and low cardiac output syndrome (r = 0.26, P = 0.03). However, there were no significant differences in ICU stay or duration of mechanical ventilation among the groups. Conclusion: TPS3 after intracardiac TOF repair is associated with higher risk of early re-intervention, highlighting the importance of close follow-up and monitoring in this patient population. Patients who develop low cardiac output syndrome in the early postoperative period may have residual defects that require prompt identification.